Infertility Stress: The Role of Coping Strategies, Personality Trait, and Social Support - Batool Rashidi; Soheila Hosseini; Pooya Beigi; Mahya Ghazizadeh; Mohammad Farahani (Tehran University of Medical Sciences, 2011)
Objective: The aim of our study was to investigate the effect of coping strategies, personality trait and social support as the main social and psychological factors on infertility stress. Materials and methods: This study was conducted on 201 infertile Iranian women referred to the Vali-e-Asr Reproductive health Research Center, and completed the following questionnaires: The fertility problem inventory, measuring perceived infertility related stress (Newton CR, 1999), big five factor personality questionnaire (Farahani, 2009), multidimensional scale of perceived social support MSPS (Zimmet 1988), and multidimensional assessment of coping (Endler, 1990).The results were then analyzed using the Pearson Correlation and stepwise regression. Results: Infertility stress has negative and significant relation with emotion-oriented coping method, perceived social support and bring extrovert. It has a positive, significant relation with emotion-oriented coping method, obsessive compulsive disorder (OCD). The results of the stepwise regression showed that emotion-oriented coping method, OCD and being extrovert are suitable predictors of infertility stress. Conclusion: About 22% of the infertility stress variance was explained by coping strategies and personality trait. Therefore our result demonstrates the importance of social and psychological factors on experiencing the infertility stress.